Challenges of neural interfaces for stroke motor rehabilitation - Vidaurre, Carmen; Irastorza-Landa, Nerea; Sarasola-Sanz, Andrea; Insausti-Delgado, Ainhoa; Ray, Andreas M.; Bibián, Carlos; Helmhold, Florian; Mahmoud, Wala J.; Ortego-Isasa, Iñaki; López-Larraz, Eduardo; Lozano Peiteado, Héctor; Ramos-Murguialday, Ander (Frontiers in Human Neuroscience, 2023)
More than 85% of stroke survivors suffer from different degrees of disability for the rest of their lives. They will require support that can vary from occasional to full time assistance. These conditions are also associated to an enormous economic impact for their families and health care systems. Current rehabilitation treatments have limited efficacy and their long-term effect is controversial.Here we review different challenges related to the design and development of neural interfaces for rehabilitative purposes. We analyze current bibliographic evidence of the effect of neurofeedback in functional motor rehabilitation of stroke patients. We highlight the potential of these systems to reconnect brain and muscles. We also describe all aspects that should be taken into account to restore motor control.Our aim with this work is to help researchers designing interfaces that demonstrate and validate neuromodulation strategies to enforce a contingent and functional neural linkage between the central and the peripheral nervous system. We thus give clues to design systems that can improve or/and re-activate neuroplastic mechanisms and open a new recovery window for stroke patients.